2003
DOI: 10.1104/pp.102.019612
|View full text |Cite
|
Sign up to set email alerts
|

Photoacoustic Analysis Indicates That Chloroplast Movement Does Not Alter Liquid-Phase CO2 Diffusion in Leaves of Alocasia brisbanensis    

Abstract: Light-mediated chloroplast movements are common in plants. When leaves of Alocasia brisbanensis (F.M. Bailey) Domin are exposed to dim light, mesophyll chloroplasts spread along the periclinal walls normal to the light, maximizing absorbance. Under high light, the chloroplasts move to anticlinal walls. It has been proposed that movement to the high-light position shortens the diffusion path for CO 2 from the intercellular air spaces to the chloroplasts, thus reducing CO 2 limitation of photosynthesis. To test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
58
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 54 publications
3
58
0
Order By: Relevance
“…This group measured oxygen diffusion times using pulsed photoacoustics (as a substitution for CO 2 diffusion) between control and strong lightirradiated Alocasia leaf samples, but they could not find any differences in CO 2 diffusion rates between the two samples (Gorton et al, 2003). Additionally, they could found no difference in the distance between the centers of the chloroplasts and the closest air spaces between two samples (Gorton et al, 2003). Another group found that blue light rapidly reduced CO 2 diffusion from intercellular air spaces to the chloroplasts in both Nicotiana and Platanus leaves and that this reduction was completed before chloroplasts finished the avoidance movement to the aniticlinal walls (Loreto et al, 2009).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
See 4 more Smart Citations
“…This group measured oxygen diffusion times using pulsed photoacoustics (as a substitution for CO 2 diffusion) between control and strong lightirradiated Alocasia leaf samples, but they could not find any differences in CO 2 diffusion rates between the two samples (Gorton et al, 2003). Additionally, they could found no difference in the distance between the centers of the chloroplasts and the closest air spaces between two samples (Gorton et al, 2003). Another group found that blue light rapidly reduced CO 2 diffusion from intercellular air spaces to the chloroplasts in both Nicotiana and Platanus leaves and that this reduction was completed before chloroplasts finished the avoidance movement to the aniticlinal walls (Loreto et al, 2009).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
“…Senn (1908) hypothesized that this positioning might result from the chemotaxis of chloroplasts to the CO 2 in air spaces. Using different approaches and plant species, three groups examined whether chloroplast photorelocation movement, especially the avoidance response, influenced CO 2 diffusion in leaves (Gorton et al, 2003;Loreto et al, 2009;Tholen et al, 2008). One research group hypothesized that chloroplast distribution on the anticlinal walls by the avoidance response facilitated CO 2 utilization by shortening the CO 2 diffusion path length from air spaces to the mesophyll chloroplasts (Gorton et al, 2003).…”
Section: Influence Of the Chloroplast Avoidance Response On Co 2 Diffmentioning
confidence: 99%
See 3 more Smart Citations